Bedside healthcare rationing dilemmas: A survey from Croatia - Pinho, Micaela (2018)
Purpose – The purpose of this paper is to explore Croatian views about issues regarding bedside rationing decisions. Design/methodology/approach – An online questionnaire was used to collect data from a sample of 243 Croatian citizens. In a context of hypothetical scenarios involving priority setting decisions taking by physicians, the present study elicits Croatian respondents’ views concerning: the ethical principles that should guide patients prioritization; the parties that should make prioritization decisions; and the likelihood of healthcare rationing becoming a reality. Descriptive analysis, factor analysis and parametric and non-parametric tests were performed. Findings – Findings suggest that Croatian respondents: support multiple substantive rationing criteria, with an incident in favoring the worst-off, reducing inequalities in health, translated in the fair-innings argument and efficiency achievement; appoint health professionals as rationing decision makers; and do not seem to believe in the possibility of patient selection becoming a reality. Practical implications – Favoring the worst-off, equalizing life time health and the pursuit of efficiency seem to be the criteria most preferred by Croatian respondents to guide rationing policy at the micro level. Originality/value – This study is the first attempt to elicit Croatian opinions concerning several rationing criteria inherent in healthcare micro allocation decisions. Healthcare rationing is a serious challenge to Croatian policy makers and so it would be useful for the public’s perceptions and beliefs to be considered.